Identity and agency in school and afterschool settings: Investigating digital media’s supporting role - Katie Davis; Anthony Ambrose; Mania Orand (Digital Culture & Education, 2017)
This study documents opportunities for identity and agency experienced by students in urban school and afterschool contexts, with a focus on digital media’s role in shaping these opportunities. We conducted focus groups and interviews with 43 students and six teachers affiliated with an urban public high school and a network of afterschool programs in the United States, as well as participant observations of nine afterschool sessions and three school classes. Compared to school, afterschool programs afforded students greater opportunities for identity expression, with digital media generally playing a supporting role. We found that the institutional constraints and sociopolitical dynamics that shape students’ experiences in school and afterschool contexts are largely mirrored in the ways technology is used in these contexts. Introducing digital media into a setting will not necessarily change these dynamics, though we did see potential for disruption in some afterschool settings. The findings provide new insight into digital media’s role in supporting identity and agency in school and afterschool settings.